Garcinia mangostana L. Nanoextract Improves Early Inflammatory Phase Bone Fracture Healing in Diabetes Mellitus by Targeting IL-1β and TNF-α: A Comprehensive Meta-Analysis - Gregorius Gathot Garudanto; Yuriz Bakthiar; MI Widiastuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Diabetic fracture healing is often impaired due to prolonged and exaggerated inflammation, characterized by elevated levels of pro-inflammatory cytokines like IL-1β and TNF-α. Garcinia mangostana L. (mangosteen) has demonstrated anti-inflammatory properties, and nanoformulations may enhance its bioavailability and efficacy. This meta-analysis aimed to evaluate the effect of Garcinia mangostana L. nanoextract on IL-1β and TNF-α levels during the early inflammatory phase of fracture healing in diabetic models. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library databases for studies published between 2013 and 2024. Studies investigating the effects of Garcinia mangostana L. nanoextracts on IL-1β and TNF-α levels in in vivo or in vitro models of diabetic fracture healing were included. Data on cytokine levels, fracture healing parameters (where available), and study characteristics were extracted. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Heterogeneity was assessed using the I² statistic. Results: Nine studies met the inclusion criteria. Meta-analysis revealed that Garcinia mangostana L. nanoextract significantly reduced IL-1β levels (SMD = -2.85, 95% CI: -3.97 to -1.73, p < 0.00001; I² = 88%) and TNF-α levels (SMD = -2.14, 95% CI: -3.08 to -1.20, p < 0.00001; I² = 82%) compared to control groups in diabetic fracture healing models. Subgroup analyses indicated significant reductions in both in vivo and in vitro studies. Conclusion: This meta-analysis provides evidence that Garcinia mangostana L. nanoextract significantly reduces IL-1β and TNF-α levels during the early inflammatory phase of fracture healing in diabetic models. These findings suggest that Garcinia mangostana L. nanoextract holds therapeutic potential for improving fracture healing outcomes in individuals with diabetes mellitus.